(untitled) (Journal of Economic Research & Business Administration, 2021)
The study investigated the nexus between structural capital efficiency and agency conflicts using sample of sixty-six (66) non-financial firms listed on the Nigerian Stock Exchange between 2010 and 2019. These 660 firm-year observations were extracted from the annual reports of the sample firms for various years. Agency costs is proxy with asset turnover rate and operating expense ratio as alternative measure for robustness analysis. Structural capital efficiency was obtained following Pulic (2000) estimation of value-added intellectual capital coefficient. Descriptive statistics tools of mean and standard deviation as well as bi variate tool of correlation coefficients were used for preliminary analysis of the study. The hypotheses were tested using panel feasible generalized least square regression. The results of the analysis reveal that structural capital efficiency has significant positive impact on asset turnover rate while it has significant negative impact on operating expense ratio implying that results obtained are robust to alternative proxy for agency costs. It is therefore recommended that the management who wish to satisfy the interest of their principal can leverage on the efficiency of their structural capital to achieve the goal. In addition, the shareholders should monitor the efficiency of structural capital in their subscribed firms since it automatically helps to limit the agency problem. Also, potential investors should consider the efficiency of the structural capital within a firm in making their investment decisions. Key words: agency costs, agent, non-financial firms, principal, structural capital efficiency.